Demokrasiye geçiş sürecinde Türkiye’de sol basın (1945-1950) - Efe, Eren (My University, 2016)
DEMOKRASİYE GEÇİŞ SÜRECİNDE TÜRKİYE’DE SOL BASIN Bu çalışmada 1945-1950 arasında Türkiye’de yayınlanan sol yayın organları incelenmektedir. Çalışmanın temel amacı, 1945’te çok partili hayata geçişle birlikte Türkiye’nin liberalleştiği ve bu bağlamda basın özgürlüğünün geliştiği ifade edilen bu dönemde, hem rejimin sol basın karşısındaki tavrını hem de sol basın ve sosyalist hareketin bu süreçten nasıl etkilendiğini, süreci algılayışını ve dönemin siyasal aktörleriyle olan ilişkisini yine sol basın üzerinden belirlemektir. 1945 sonrasında, yasal düzenlemelerin de olanak sağlamasıyla birlikte sosyalist hareket, siyasal parti, sendika ve bunlar çerçevesinde çıkarılan yayın organları ile tek parti döneminin aksine oldukça yaygın ve görünür bir örgütlenme sürecine girmiştir. Çok partili yaşama geçişin, sol hareket tarafından öze ait ve kalıcı olarak algılanmasına dayanan bu faaliyetler oldukça kısa bir dönem devam edebilmiş, siyasi parti, sendika ve basın organlarının tümü kapatılmıştır. Genel olarak sosyalist hareket ve özel olarak sol basın, liberal bir sistemin asgari gerekleri olan basın ve örgütlenme özgürlüğünü kullanamamış, tüm süreç boyunca baskılara maruz kalmıştır. CHP karşısında liberal bir programa sahip olan DP ise süreç boyunca sol harekete karşı CHP ile benzeşen bir anlayışa sahip olmuştur. Çalışmada, çok partili hayat geçişle birlikte arzulanan demokrasinin, sol hareketi ve bu hareketin basın yayın organlarını içeren bir süreç olmadığı öne sürülmektedir. Bu durumun yanı sıra dönem değerlendirmelerinde yok sayılmasına rağmen sosyalist hareket ve sol basının sürecin şekillenmesinde oldukça önemli etkileri olduğu savunulmaktadır. Bu çalışma için dönem boyunca yayınlanan 10 sol yayın organının 195 sayısı nitel içerik analizi yöntemi ile incelenmiştir. Sol Basın, Sendika, DP, TSEKP, TSP

LEFTİSTS PRES IN TURKEY DURING TRANSITION TO DEMOCRACY In this study, the leftist media organs which have been published in Turkey between the years 1945 and 1950 are examined. In this period, it is stated that Turkey was liberalised and freedom of the press was improved with transition to multi-party system in 1945. The main aim of the study is to determine the attitude of regime against the leftist press and also how the leftist press and socialist movement perceived and affected by this process and to analyze the relationship between political actors, leftist press and socialist movement. Socialist movement has entered into the process of organization with the aid of opprtunities provided by legal arrangements and with political parties, unions and the media organs which have been published in this framework. The organization process was very widespread and apparent contrary to one-party period. These activities were built upon the perceiving of transition to multi-party system as permanent. But this process has ended after a short time and all political parties, unions and media organs were shut down. Socialist movement and especially leftist press were not able to use freedom of organization and press which are minimum requirements in a democratic system and they were exposed to oppression during all period. DP that had a more liberal program in comparison to CHP, had a similar understanding with CHP against leftist movement during the process. This study asserts that the desired democracy with transition to multi-party system was not a process involving the leftist movement and its media organs. Besides it is argued that socialist movement and leftist press have significant influence on configuration of process even they are ignored when evaluating the political period. The study analyzes 10 leftist media organs and their 195 issues published in this period by using qualitative content analysis method. a similar understanding with CHP against leftist movement during the process. This study asserts that the desired democracy with transition to multi-party system was not a process involving the leftist movement and its media organs. Besides it is argued that socialist movement and leftist press have significant influence on configuration of process even they are ignored when evaluating the political period. The study analyzes 10 leftist media organs and their 195 issues published in this period by using qualitative content analysis method. Leftist Press, DP, TSEKP, TSP
Keywords: Basın; Çok partili döneme geçiş (1945-1950); Siyasi yönler; Tarih; Türkiye